JALAN TERJAL KADERISASI MUHAMMADIYAH PTMA DI BANDUNG: Pendekatan Konsep Pendidikan Buya Hamka dan Relevansinya dengan Sistem Perkaderan Muhammadiyah - Selamet, Sopaat Rahmat; Amrullah, Fahmi (Fakultas Agama Islam Universitas Muhammadiyah Bandung, 2023)
The Muhammadiyah cadres in PTMA Bandung City, such are UM Bandung and UNISA, have not provided maximum cadre contribution. There are still many lecturers and structural leders at PTMA who cannot become driving cadres at various levels, be it PDM, PCM, or PRM. This research aims to (1) To determine the problems of cadres formation in the AUM environment, namely PTMA in Bandung, and its impact on the development of Muhammadiyah in society in Greater Bandung (2) To determine the condition of cadres in the PTMA environment in Bandung in the study of educational theory and Buya Hamka cadre formation. This research uses a mixed-method approach. The results shows that the cadre formation process in the PTMA environment in Greater Bandung is still not optimal as expected by the Buya Hamka concept as an institution that produces maximum cadres of the people, nation and humanity. Also, before the idealist outlined by the PP Muhammadiyah Research and Development Higher Education Council and the Cadre Education Council. Keywords: Regeneration; Muhammadiyah; Education